Research On Problems and Countermeasures of Social Basic Endowment Insurance Collection of Small, Medium and Micro Enterprises - Lu, Fang (International Journal of Management and Education in Human Development, 2022)
With the continuous deepening of China's reform and opening up and the continuous development of the socialist market economy, the private economy, especially small, medium, and micro enterprises, play an increasingly important role in social and economic life and has gradually developed into a new force of the national economy. By the end of 2018, the number of small, medium, and micro enterprises in China had exceeded 100 million, accounting for 99.7% of the total number of enterprises in China. The status of small, medium-sized, and micro enterprises in China's economic development is becoming more and more prominent. However, what is extremely disproportionate is that the current situation of social security in small, medium-sized, and micro enterprises is not optimistic. The vast majority of bosses and employees of small, medium-sized, and micro enterprises are actively or passively outside the scope of social security so that the employees of small, medium-sized, and micro enterprises can not get basic living security, It limits the orderly development of small, medium-sized and micro enterprises. Therefore, it is imperative to reasonably solve the social insurance problem of small, medium-sized, and micro enterprises/